-38+9+y=-12+16

Simple and best practice solution for -38+9+y=-12+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -38+9+y=-12+16 equation:


Simplifying
-38 + 9 + y = -12 + 16

Combine like terms: -38 + 9 = -29
-29 + y = -12 + 16

Combine like terms: -12 + 16 = 4
-29 + y = 4

Solving
-29 + y = 4

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '29' to each side of the equation.
-29 + 29 + y = 4 + 29

Combine like terms: -29 + 29 = 0
0 + y = 4 + 29
y = 4 + 29

Combine like terms: 4 + 29 = 33
y = 33

Simplifying
y = 33

See similar equations:

| 5(x-6)-6x(x-5)=x+5-(x-4) | | 1900+5x=2 | | 17x-5=14x-8 | | 7/22x11/35 | | y=2x+5cos^3x | | -3(x+4)=2(x-5) | | 0=x^4-3x^3-8x^2+12x+16 | | 3x-2=-2x-8 | | 30x=6x | | -5(4x+1)-5=-3(x+4)+2x | | 15-6n+2=4n-1 | | y=xsquared+1 | | 11x+13=55 | | -10z=2.7 | | 4-3m=-4m+5 | | 15x=11000 | | 10-6=4 | | 10z=2.7 | | Y=(x-2)squared | | 41790=5+210t | | 8g-4=5(2g+1) | | 4x+7=2x+47 | | 3/2*7/3 | | 65=5+2.5x | | 36+b^2=324 | | (2/9x)-(1/7)=(1/6) | | 6x+4x-4=26 | | 5(4x+5)=-13+18 | | 11x+13=58 | | 3x+25-9=0 | | (4/5x)=-12 | | 2m+4m-3m=24 |

Equations solver categories